Impact of Probiotics on Dairy Production Efficiency - Nalla, Kirankumar; Manda, Naresh Kumar; Dhillon, Harmeet Singh; Kanade, Santosh R.; Rokana, Namita; Hess, Matthias; Puniya, Anil Kumar (Frontiers in Microbiology, 2022)
There has been growing interest on probiotics to enhance weight gain and disease resistance in young calves and to improve the milk yield in lactating animals by reducing the negative energy balance during the peak lactation period. While it has been well established that probiotics modulate the microbial community composition in the gastrointestinal tract, and a probiotic-mediated homeostasis in the rumen could improve feed conversation competence, volatile fatty acid production and nitrogen flow that enhances the milk composition as well as milk production, detailed changes on the molecular and metabolic level prompted by probiotic feed additives are still not understood. Moreover, as living biotherapeutic agents, probiotics have the potential to directly change the gene expression profile of animals by activating the signalling cascade in the host cells. Various direct and indirect components of probiotic approaches to improve the productivity of dairy animals are discussed in this review.